The economics of higher education and tests of equity criteria in Turkey - Erk, Nejat [Verfasser] (My University, 1989)
"Unequal opportunities are a fact of life in most societies. Imbalances exist in each society under all conceivable economic environments. To alleviate these imbalances, most governments tend to interfere in the market. In this respect Turkey is no exception. Thus, the government established the Turkish Higher Education Council in 1982 with the hope of improving educational resource allocation. This paper investigates the private costs of public higher education in Turkey. It also tests whether a structural cost difference exists between the universities in the three biggest cities of Turkey and the rest of the country's fifteen Universities. Does the highly subsidized Turkish Higher Education ensure equity of resource allocation? The findings show that, among the factors contributing to higher education, the number of faculty members has the lowest price elasticity of demand. In the case of assessing whether there are structural cost differences between the universities in developed and underdeveloped regions the findings show that imbalances between the two regions still exist." (author's abstract) ((en)) Der Artikel untersucht die privaten Kosten des öffentlichen Hochschulssystems in der Türkei. Es wird auch überprüft, ob strukturelle Kostenunterschiede zwischen den drei grössten türkischen Universitäten und den übrigen fünfzehn Universitäten bestehen. Garantiert das hochsubventionierte Hochschulsystem Gerechtigkeit bei der Mittelverteilung? Bei der Bewertung stellt sich heraus, dass immer noch Ungleichgewichte zwischen den Regionen bestehen. (IAB)
Wirtschaftliche Aspekte der Hochschulausbildung und Gerechtigkeitskriterien in der Türkei
Keywords: T 4.6 Wirtschafts- und Rechtswissenschaften; P 2.1.5 Fachhochschul- und Hochschulreife; S 4 Kosten & Finanzierung; G 2.1.4 Regionalisierung; G 2.1.1 Ökonomie / Märkte; Bildungsökonomie; Hochschulsystem; Hochschule; Kosten; Regionale Verteilung; Hochschulpolitik; Bildungsinvestition; Finanzierung; Quantitative Angaben